2015
DOI: 10.1007/s11661-015-3087-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Strength Recovery in Welds of NUCu-140 Steel Through Multipass Welding and Isothermal Post-Weld Heat Treatments

Abstract: NUCu-140 is a ferritic copper precipitation-strengthened steel that is a candidate material for use in many naval and structural applications. Previous work has shown that the heat-affected zone (HAZ) and fusion zone (FZ) of NUCu-140 exhibit softening that is due to dissolution of the copper-rich precipitates. This study aims to recover the FZ and HAZ strength by re-precipitation of the copper-rich precipitates through either multiple weld passes or an isothermal post-weld heat treatment (PWHT). The potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A peak temperature of 1350 °C was chosen to promote rapid austenite grain growth resulting in a CGHAZ with a low impact and fracture toughness. [18,19] The specimens were heated to 1350 ∘ C at 400 ∘ C/s where they were held for one second before rapid cooling at 50 or 15 ∘ C/s. These cooling rates correspond to t8/5 times of 6 and 20s.…”
Section: Methodsmentioning
confidence: 99%
“…A peak temperature of 1350 °C was chosen to promote rapid austenite grain growth resulting in a CGHAZ with a low impact and fracture toughness. [18,19] The specimens were heated to 1350 ∘ C at 400 ∘ C/s where they were held for one second before rapid cooling at 50 or 15 ∘ C/s. These cooling rates correspond to t8/5 times of 6 and 20s.…”
Section: Methodsmentioning
confidence: 99%
“…A peak temperature of 1350 °C was chosen to promote rapid austenite grain growth resulting in a CGHAZ with a low impact and fracture toughness. [16,17] The test specimens used in the Gleeble tests were cut parallel to the longitudinal rolling direction of rolled plates with dimensions 10x5x55 mm for the Charpy V impact testing and 120xØ6 mm for the tensile testing.…”
Section: Gleeble Simulationsmentioning
confidence: 99%
“…In particular, the precipitation of coherent nanoparticles, such as body-centered cubic (bcc) Cu-rich nanoclusters [2][3][4][5][9][10][11][12] and B2-ordered NiAl intermetallic nanoparticles [13][14][15][16][17], is very appealing, because they can precipitate on a sufficiently fine scale (less than 5 nm in diameter), providing an extremely high strengthening response. Currently, research is starting to emerge on the weldability of this class of high-strength steels, mostly of Cu-rich nanoclusters strengthened steels [18][19][20][21][22][23]. Previous welding studies showed that the hardness of heat-affected zone (HAZ) and fusion zone (FZ) of Cu-strengthened steels was undermatched to the base metal (BM), which was considered to be due to the partial dissolution of preexisting Cu-rich nanoclusters within the HAZ and full dissolution of nanoclusters within the FZ, as characterized by atom probe tomography (APT) [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous welding studies showed that the hardness of heat-affected zone (HAZ) and fusion zone (FZ) of Cu-strengthened steels was undermatched to the base metal (BM), which was considered to be due to the partial dissolution of preexisting Cu-rich nanoclusters within the HAZ and full dissolution of nanoclusters within the FZ, as characterized by atom probe tomography (APT) [18][19][20][21]. It has been found that the reprecipitation of nanoparticles can be achieved by designing an appropriate post-weld heat treatment (PWHT) or multi-pass welding procedure, which provides a promising way to recover the mechanical properties of welds [22,23].…”
Section: Introductionmentioning
confidence: 99%